The Effect of Environmental Performance on Firm Value: Role of Profitability - Tunggadi, Michel; Kampo, Kunradus (AJAR, 2025)
This study aims to analyze environmental performance's effect on firm value and profitability can moderate the effect of environmental performance on firm value. This study uses stakeholder theory and signaling theory. This study uses secondary data. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange during the 2021-2023 period. The number of companies that met the sampling criteria was 33 companies with a total sample of 99. The data analysis technique for this study was carried out using the Statistical Package for the Social Sciences (SPSS) software. The results of this study indicate that environmental performance has a significant effect on firm value. The results of this study also indicate that profitability can moderate the effect of environmental performance on firm value.